Correlation of biomarkers and bone mineral density for osteoporosis in post-menopausal women - Hymavathi, K.; Jakka, Tejaswini; Paturi, Bhaavya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Osteoporosis is a metabolic bone disorder characterised by a low bone mass and microarchitectural deterioration of bone tissue followed by enhanced bone fragility and a consequent rise in fracture risk. Aim of the study is to correlate the biomarkers and bone mineral density in postmenopausal osteoporosis. Methods: This is a prospective study done in the department of obstetrics and gynaecology, Narayana medical College and Hospital, Nellore for a period of 2 years (October 2016-October 2018). This study was designed to assess the correlation between bone mineral density (BMD) and various biochemical markers. Results: The mean age of the present study is 60.51±9.35 years. There is a significant correlation found between age, serum phosphorus, urinary OHPr and bone mineral density. The mean BMI of the present study is 24.75±4.25 kg/m2. There is a significant correlation observed between BMI, serum ionized calcium, urinary OHPr and bone mineral density. There exists a significant correlation between BMD and urinary OHPr. It is found that in menopausal women spine and hip are the major sites affected by osteoporosis. The early changes are found in lumbar spine compared to hip. In the present study with increase in BMI there is increase in BMD signifying obesity is a protective factor for osteoporosis leaving aside all it’s ill effects. Urinary hydroxyproline a marker of resorption is found to have a negative correlation with BMD. Conclusions: BMD measurements using DEXA are not readily available in India. Biochemical markers of bone remodelling are useful tools in assessment of osteoporosis and are safe, inexpensive, easily performed. In the present study an attempt is made to correlate biochemical markers and BMD so as to detect osteoporosis even before the changes being evident on imaging studies.